Character Education In The Common People Novels By Andrea Hirata - Widodo, Joko (JOLADU: Journal of Language Education, 2023)
Character education is a crucial aspect of all circles of society, especially for children. This study aims to describe the form and impact of character education, hard work, and social care in the Common people novels by Andrea Hirata. The research was studied using a literary sociology approach. The source of data in this study is the Common people novels by Andrea Hirata, paying attention to the unit of story, sentences, actions, thoughts, and narratives in the novel. The data found is processed through several steps: determining the source, collecting data, grouping data, and assigning a code number to the research instrument table. Data analysis techniques are carried out in several stages: simplification, data checking, data presentation, and conclusions. The results of this study show that various forms of character education were found. The forms of character education are hard work, practice seriously, full of confidence, passion, and never giving up. The form of social care character education is to assist others and respect others. This research shows that literary works can be a means of learning character education for readers. This is because literary works are a mirror of the reality of life.